Proceedings of the 1st International Conference on Advanced Multidisciplinary Research (ICAMR 2018) 2019
DOI: 10.2991/icamr-18.2019.35
|View full text |Cite
|
Sign up to set email alerts
|

The Misconception of Stoichiometry and Its Impact on the Chemical Equilibrium

Abstract: Misconception about stoichiometry and its impact on the chemical equilibrium concept were studied on 245 second-grade students at SMA Negeri 2 Gowa, South Sulawesi, Indonesia. Research instruments were Stoichiometry misconception test (SMT) and chemical equilibrium misconception three tier tests (CEMTT). Semi structured interview was conducted after the administration of the test for fifteen students. SMT consisted of ten items with high validity of 90.70% and reliability coefficient, calculated using Cronbach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Usu (2019), Siswaningsih (2019), andHarza (2021) argued that students often experience misconceptions about chemical equilibrium, especially in the dynamic equilibrium subtopic. Siswaningsih (2017), Jusniar (2019), Yamtinah (2019), Khairunnisa & Prodjosantoso (2020), Andriani, et al, (2020), and Jusniar (2020 suggested that apart from dynamic equilibrium, misconceptions about chemical equilibrium also occur in the sub-topics of equilibrium shifts and equilibrium constants. The research results regarding misconceptions about other chemical equilibriums developed by Omilani and Elebute (2020) suggest that misconceptions about chemical equilibrium material also occur in the sub-topic of factors that influence shifts in equilibrium.…”
Section: Introductionmentioning
confidence: 99%
“…Usu (2019), Siswaningsih (2019), andHarza (2021) argued that students often experience misconceptions about chemical equilibrium, especially in the dynamic equilibrium subtopic. Siswaningsih (2017), Jusniar (2019), Yamtinah (2019), Khairunnisa & Prodjosantoso (2020), Andriani, et al, (2020), and Jusniar (2020 suggested that apart from dynamic equilibrium, misconceptions about chemical equilibrium also occur in the sub-topics of equilibrium shifts and equilibrium constants. The research results regarding misconceptions about other chemical equilibriums developed by Omilani and Elebute (2020) suggest that misconceptions about chemical equilibrium material also occur in the sub-topic of factors that influence shifts in equilibrium.…”
Section: Introductionmentioning
confidence: 99%
“…It can hinder understanding the next concept that is built on it. The following research by Jusniar et al, (2019) stated that misconceptions in stoichiometry (prerequisite concepts) could cause students to have difficulty understanding the material of chemical equilibrium and subsequently lead to misconceptions.…”
Section: Introductionmentioning
confidence: 99%
“…Rohmah chemistry that requires understanding qualitative and quantitative aspects related to chemical phenomena to solve various chemical problems in high schools and colleges (Sunyono, 2015). Stoichiometry is a chemical calculation that must be understood correctly because it underlies other chemical concepts, namely moles, chemical equilibrium (Jusniar et al, 2019) Based on the results of interviews with several chemistry teachers and students, it is known that students have difficulty in understanding the material because many concepts are abstract and mathematical calculations that make students confused. Misconceptions perhaps highly resistant to change, fixed for years, and unaffected by classroom teaching (Luoga et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Such difficulties can cause students to encounter misconception in stoichiometry (Nilawati, 2016) A misconception is a mismatch of students' understanding of science agreed upon by scientists (Barke et al, 2009;Mondal, B. et al, 2013). Misconception can be caused by teacher explanations, textbooks, and students' prior knowledge (Jusniar et al, 2019;Kelly et al, 2019).…”
Section: Introductionmentioning
confidence: 99%